2015
DOI: 10.1080/00222895.2014.971700
|View full text |Cite
|
Sign up to set email alerts
|

Attentional Demands of Perturbation Evoked Compensatory Stepping Responses: Examining Cognitive-Motor Interference to Large Magnitude Forward Perturbations

Abstract: The authors examined the cognitive-motor interference of reactive balance control under dual-task condition in young healthy adults. Sudden large forward perturbations were delivered in stance position with (dual-task) and without (single-task balance) a working memory task. This task was also performed in quiet stance (single-task cognition). Dual tasking significantly reduced postural stability and compensatory step length, and delayed the reaction time. The significant linear correlation between postural st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
22
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(26 citation statements)
references
References 43 publications
(55 reference statements)
4
22
0
Order By: Relevance
“…Although non-significant, these trends were consistent with those identified in healthy young, healthy older, and balance-impaired older adults [16, 17, 18]. When examining the responses from the three types of trials, the general trends were for performance to improve from the first usual-response trial to the later usual-response trials, and then to worsen from the later usual-response trials to the dual-task trial (i.e.…”
Section: Resultssupporting
confidence: 73%
See 2 more Smart Citations
“…Although non-significant, these trends were consistent with those identified in healthy young, healthy older, and balance-impaired older adults [16, 17, 18]. When examining the responses from the three types of trials, the general trends were for performance to improve from the first usual-response trial to the later usual-response trials, and then to worsen from the later usual-response trials to the dual-task trial (i.e.…”
Section: Resultssupporting
confidence: 73%
“…The effects of dual-task scenarios on reactive balance tasks have been examined in healthy young, healthy older, and balance-impaired older adults [16, 17, 18]. Overall, the addition of a cognitive task generally results in decrements in performance of reactive balance tasks.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…obstacle in the way, or mis-predicting the height of a step) is also of recent interest. This has been investigated during goal-directed upper extremity reaching (Cheng et al, 2013;Taylor & Thoroughman, 2007), or a sliding platform to induce a slip while standing (Bhatt, Yang, & Pai, 2012;Nnodim et al, 2015;P. J. Patel & Bhatt, 2015;Pavol, Runtz, Edwards, & Pai, 2002;Zettel, McIlroy, & Maki, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…These have revealed that motor responses are in competition with cognitive responses by the detection of delays in either a stepping reaction to a balance perturbation (Little & Woollacott, 2015;Sun & Shea, 2015), or delays in cognitive response (Nnodim, Kim, & Ashton-Miller, 2015; P. J. Patel & Bhatt, 2015) when prioritizing stability (motor response) over the cognitive task.…”
Section: Cognitive-motor Dual-task Trainingmentioning
confidence: 99%